Os muitos sentidos compartilhados: Bakhtiniana e a Jornada comemorativa de seus 15 anos - Brait, Beth; Cruz Pistori, Maria Helena; Lopes, Bruna; Stella, Paulo Rogério; Godinho de Alcântara, Regina; Pucci Faria Penteado e Silva, Adriana (Bakhtiniana. Revista de Estudos do Discurso, 2024)
Editorial 19.4